2016
DOI: 10.1186/s13063-016-1617-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics (Vivomixx®) in obese pregnant women and their newborn: study protocol for a randomized controlled trial

Abstract: BackgroundMaternal obesity is associated with increased risks of adverse pregnancy-related complications and outcomes for both mothers and infants. Overweight and obese women have an increased risk of pregnancy-induced hypertension, preeclampsia and gestational diabetes mellitus (GDM). Infant Body Mass index (BMI) and the risk of obesity in adulthood are related to maternal gestational weight gain (GWG). Preventive lifestyle and dietary interventions are time-consuming and do not always reduce GWG or the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
0
22
0
3
Order By: Relevance
“…bulgaricus DSM 24734, L. acidophilus DSM 24735, L. paracasei DSM 24733, and L. plantarum DSM 24730; 4.5 × 10 10 CFU in total) from 14-20 weeks of gestation until the delivery of the baby. After the detailed analysis of blood, urine, fecal samples, and diet profile and weight gain, it has been proved that the supplementation of Vivomixx® significantly reduced the weight gain during the pregnancy period and reduced the pregnancy complications via positive alteration of GM of obese pregnant women [31].…”
Section: Influence Of Probiotic Supplementation On Health Status Omentioning
confidence: 99%
“…bulgaricus DSM 24734, L. acidophilus DSM 24735, L. paracasei DSM 24733, and L. plantarum DSM 24730; 4.5 × 10 10 CFU in total) from 14-20 weeks of gestation until the delivery of the baby. After the detailed analysis of blood, urine, fecal samples, and diet profile and weight gain, it has been proved that the supplementation of Vivomixx® significantly reduced the weight gain during the pregnancy period and reduced the pregnancy complications via positive alteration of GM of obese pregnant women [31].…”
Section: Influence Of Probiotic Supplementation On Health Status Omentioning
confidence: 99%
“…Supplementation with L. rhamnosus GG and B. lactis ( per day) from the first-trimester pregnancy up to 6 months after delivery in combination with a diet can counteract obesity and reduce metabolic disorders [ 75 ]. Additionally, the study showed long-term benefits and safety associated with the intervention used, among others reducing the risk of GDM in women at high risk [ 76 , 123 ]. On the other hand, there was no effect of L. salivarius UCC118 ( CFU per day) on body weight during four-week supplementation in women in the first trimester of pregnancy [ 77 ].…”
Section: Review Of Clinical Studies Using Probiotics In Obesitymentioning
confidence: 99%
“…c A rate of intake ≥ 80% is similar to other (pilot) RCTs with probiotics and food supplements in pregnant and non-pregnant individuals [34, 35]…”
Section: Methodsmentioning
confidence: 60%
“… a In case one or more progression criteria are not met, revisions to the study protocol should be considered prior to conducting the full randomized controlled trial (RCT) b A rate > 90% is comparable to previous RCTs in pregnant women with depressive and anxiety symptoms [32, 33] c A rate of intake ≥ 80% is similar to other (pilot) RCTs with probiotics and food supplements in pregnant and non-pregnant individuals [34, 35] d The rates of adherence to vaginal and fecal sampling and hair-sampling protocols do not include unforeseen errors, for example, loss of biological samples due to storage problems, etc*Key progression criteria…”
Section: Methodsmentioning
confidence: 99%